Evaluation of an andean common bean reference collection under drought stress (2011)
More than 60% of common bean (Phaseolus vulgaris L.) production worldwide is impacted by the risk of drought. In this study, the goal was to evaluate 64 bush bean genotypes from the CIAT reference collection to identify possible sources of drought resistance in the Andean gene pool. Phenotypic traits such as yield, 100-seed weight (P100) and days to physiological maturity (Dpm) were evaluated on selected accessions of this collection which was grown in an 8x8 lattice with two repetitions under three environments: intermittent drought (SI) and irrigation (R) in Palmira as well as early drought (ST) in Darién, Colombia. The genotypes included 20 from the Nueva Granada 1 (NG1) sub-race, 19 from the Nueva Granada 2 (NG2) sub-race, 10 from race Peru (P), 14 Andean control genotypes and one Mesoamerican check. The variables were analyzed through a combined ANOVA across environments, while simple correlations between yield and others variables were determinate. The genotypes with better adaptation to drought showed higher yields, 100-seed weight and fewer days to physiological maturity. The coefficients of correlations among yield and 100-seed weight were significant and positive, while Dpm showed negative correlation. Fourteen genotypes were identified as drought tolerant: G4001, G5625, G6639, G16115, G17070, G18255, G21210 and G22247 from the NG1 sub-race; G5708, G14253, G18264 and LRK31 from the NG2 sub-race; and DRK47 and G22147 from race Peru.